PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS TRANSMIGRASI DAN TENAGA KERJA KABUPATEN LUWU TIMUR - Nely Haryati Batara; Ris Akril Nurimansjah; Bakhtiar (JURNAL ILMIAH EDUNOMIKA, 2026)
Employee performance is a cornerstone of effective local government administration, including at the Office of Transmigration and Manpower of East Luwu Regency. However, bureaucratic dynamics often influenced by non-technical factors such as personal favoritism in promotions and low transparency in human resource policies pose significant challenges to sustaining optimal performance. This study aims to examine both the simultaneous and partial effects of job satisfaction and organizational climate on employee performance. Employing a quantitative approach, the research surveyed the entire population of 45 civil servants (census sampling) using a Likert-scale questionnaire. Data were analyzed through multiple linear regression. The results indicate that organizational climate has a positive and statistically significant effect on employee performance, whereas job satisfaction exerts a negative and statistically insignificant effect. Collectively, the two variables explain 36.4% of the variance in employee performance. This finding reveals a paradox: high levels of social comfort (hygiene factors) alone are insufficient to enhance performance without a fair, merit-based reward and promotion system (motivator factors). The study concludes that human resource management reform should prioritize strengthening organizational climate and implementing meritocratic promotion practices, rather than focusing solely on conventional job satisfaction initiatives. Keywords : job satisfaction, organizational climate, employee performance, local bureaucracy, Herzberg’s Two-Factor Theory,]